Quotes and Images From The Works of Gilbert Parker - Parker, Gilbert, 1862-1932; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2004)
"Quotes and Images From The Works of Gilbert Parker" by Gilbert Parker is a collection of thoughtful quotations and reflections likely crafted during the early 20th century. This book serves as a compilation of observations on human nature, relationships, and society, showcasing Parker's ability to blend keen insights with poetic expression. The topics explored in this collection touch on the complexities of love, the significance of memory, the nature of truth, and the myriad experiences that shape human existence. This compilation does not follow a traditional narrative structure but instead offers a rich tapestry of aphorisms and reflections that encapsulate the essence of human emotion and thought. The quotes range from poignant to sardonic, addressing themes like the futility of existence, the nature of happiness and sorrow, and the impact of societal norms on individual behavior. Each quote stands alone, inviting readers to ponder the deeper meanings within their brevity, thereby providing a mosaic of wisdom that resonates across different facets of life and experience. The breadth of insight makes this collection both a reflective read and a source of inspiration for those contemplating the human condition. (This is an automatically generated summary.)
Release date is 2004-08-27
Produced by David Widger
Keywords: Quotations